THE PROS AND CONS OF INTEGRATING COLLABORATIVE LEARNING INTO LESSON PLAN DESIGN - Ira Irzawati (PROGRES PENDIDIKAN, 2023)
Collaborative learning is a learner-centered approach that facilitates students to involve in a team work in order to achieve a certain goal in learning activities. This descriptive qualitative study investigated the pros and cons of integrating collaborative learning into lesson plan design from the perspectives of thirty students of primary school teacher education study program. Questionnaire and interview were used to figure out the students’ perspectives dealing with the issues. The data were collected, classified, analyzed, and interpreted. The results revealed that providing support system, developing communication skills, promoting autonomous learning, enhancing interaction, motivation, confidence, and critical thinking, and enriching knowledge, insight, and experience are among the pros of collaborative learning. Meanwhile, the cons of collaborative learning include imbalance task distribution, personal conflict, and distraction causes. Therefore, guiding, monitoring, and evaluating from the lecturer are highly required to maximize the pros and minimize the cons. It is expected that this research provides new perspectives of the utilization of collaborative learning in EFL learning activities especially lesson plan design.